Fluorescent Antibiotics: Bridging Diagnostic and Therapy in the Fight against Bacterial Infections - Tan Phuoc Ton; Richard Bright; Vi Khanh Truong; Krasimir Vasilev (Small Science, 2025)
Infections caused by pathogenic bacteria pose a significant threat to human health. Fluorescent antibiotics present an innovative material class that combines diagnostic capabilities with therapeutic effects. Fluorescent antibiotics offer a transformative strategy by combining precise visualization of bacterial activity with targeted antimicrobial action, addressing key challenges like drug resistance and rapid pathogen detection in diagnostics and treatment. This review highlights recent advances in the development of fluorescent antibiotics, focusing on chemical strategies such as click chemistry, amide bond formation, solid‐phase peptide synthesis, and epoxy‐amine addition. Also, the practical applications of these fluorescent probes, ranging from imaging, rapid detection, and real‐time visual tracking of pathogenic bacteria to the detailed study of molecular dynamics at the cellular level are discussed. The opportunity to combine detection and treatment of infectious diseases underscores the significant promise of these probes, particularly in the face of escalating antimicrobial resistance. However, despite the promise, most studies are confined to laboratory settings. To move forward, continued innovation and rigorous clinical validation will be essential to translating these promising molecular tools from laboratory research to impactful clinical applications.